Pengaruh Penambahan Air Cucian Beras terhadap Laju Pertumbuhan Spirulina sp. - Annisa Nur Safitri Utomo; Pande Gde Sasmita Julyantoro; Ayu Putu Wiweka Krisna Dewi (Current Trends in Aquatic Science, 2020)
Culture media is one of the important factors for microalgae growth. Adding fertilizer to culture media can influence the density of Spirulina sp. The use of rice water can be used as an alternative fertilizer for culture media because it is good for the growth of Spirulina sp. Rice water contains nutrients including nitrogen, phosphorus and vitamin B1. This study aims to determine the effect and determine the concentration of rice water media on the growth rate of Spirulina sp. culture. The experiment was conducted in December 2018 to January 2019 at Greath Hall of Brackishwater Aquaculture Fisheries (BBPBAP) Jepara, Central Java. The experiment used a completely randomized design (CRD) with five treatments and three replications. The test material in the study was Spirulina sp. with an initial density of 5×103 cells/ml and the fertilizer used is rice water and walne. The main parameters observed were Spirulina sp. cell density. while the supporting parameters observed were measurements of temperature, pH, DO, salinity, nitrate and phosphate. The dosage of adding rice washing water is treatment A1 (1 mL/L), A2 (3 mL/L), A3 (5 mL/L), K- (0 mL/L) and K + using walne fertilizer with an optimum dose of 0.5 mL/L. The results showed that the addition of rice water had a positive effect on the growth rate of Spirulina sp. The addition of rice water produces the optimum growth rate in treatment A1 which is equal to 0.57±0.001 cells/day. The ANOVA test results showed that the addition of rice water had a significant effect (P <0.05) on the growth rate of Spirulina sp.